Person-centered abortion care in public health facilities across four regions of Ethiopia: a cross-sectional quantitative study of client experiences - Bekalu Mossie Chekol; Sarah McCaffrey; Sally Dijkerman; Valerie Acre; Demeke Desta Biru; Abiyot Belai Mehary; Samuel Muluye (Frontiers in Reproductive Health, 2024)
IntroductionEthiopia has made remarkable progress in expanding access to and provision of comprehensive abortion care. However, complications due to unsafe abortion persist. As efforts to increase quality of comprehensive abortion care continue, evaluating service quality is critical. Although “women-centered” abortion care is a central component of Ethiopia's technical guidelines for safe abortion, research has mostly focused on access to care, availability of services, and meeting clinical criteria, rather than examining service quality from abortion clients’ perspectives. This study assesses the quality of comprehensive abortion care (CAC) in public health facilities, from clients’ perspectives, in four regions of Ethiopia to examine how person-centered care differs based on facility and service characteristics.MethodsWe conducted 1,870 client exit surveys in 2018 using structured questionnaires with women who received induced abortion or postabortion care services from 76 public health facilities across four regions: Tigray, Amhara, Oromia, and Southern Nations, Nationalities, and People's. We operationalized person-centered care by mapping 30 indicators of quality to five of the six domains in the Person-Centered Care Framework for Reproductive Health Equity developed by Sudhinaraset and colleagues (2017): dignity & respect; autonomy; communication & supportive care; trust, privacy, and confidentiality; and health facility environment. We calculated descriptive, bivariate, and multivariable statistics to examine associations between service characteristics and person-centered care.ResultsCAC clients reported high levels of person-centered care, with exceptionally positive experiences for outcomes in the dignity and respect and trust, privacy, and confidentiality domains. However, there was notable room for improving client experiences across three domains: autonomy, communication and supportive care, and health facility environment. Client-reported quality outcomes differed significantly by diagnosis (induced or postabortion care), region, health facility type, and procedure type. Clients in Amhara, clients at tertiary and primary hospitals, and clients who received postabortion care reported lower levels of person-centered care.DiscussionThe positive experiences reported by comprehensive abortion care clients bolster evidence of the impact of the Ethiopian government's strategy to increase abortion access in the public health sector. However, notable disparities exist for key subgroups, particularly those seeking postabortion care and people visiting tertiary and primary hospitals. Quality improvement efforts should concentrate on improving abortion clients’ autonomy, communication and supportive care, and the health facility environment. The Ethiopian Ministry of Health and its partners must dedicate resources to improve postabortion care quality, integration of reproductive health services within CAC, and pain management for MA clients as vital interventions.